Justicia barapaniensis, a new name for Justicia salicifolia T. Anderson (Acanthaceae) - Soumya, Puliyakode; Sunojkumar, Purayidathkandy (Phytotaxa, 2017)
Justicia salicifolia Anderson (1867: 514) was originally described based on specimens collected from Khasia hills of Meghalaya, India. It was used in many floras for more than a century (e.g. Clarke 1885, Perkins 1904, Gamble 1921, Merrill 1923, Benoist 1936, Graham 1988, Kartikeyan et al. 2009). However, the Anderson’s name is a later homonym of Justicia salicifolia Blume (1826: 787) and hence illegitimate. Studies in consultation with both the type materials revealed that the name Justicia salicifolia was applied to two different taxa. Therefore, a new name is proposed here for the later homonym.